ODONTOASIS, objeto de aprendizaje sobre Análisis de la Situación de Salud: componente dental. - Torrecilla Venegas, Rolando; Castro Gutiérrez, Irma (Revista Cubana de Informática Médica)
Introduction: the Stomatology career uses Information and Communication Technologies in the educational teaching process, an example of which is the increasing and progressive insertion of educational software. Objective: to develop a multimedia learning object on Analysis of the Health Situation: Dental Component. Methods: a technological innovation study was carried out in the period from February to July 2018 at the University of Medical Sciences of Sancti Spíritus. Programs such as MatchWare Mediator 9.0, HotPotatoes 6, Microsoft Office 2010, Adobe Photoshop CS version 8.0.1, were used for the design and development of the multimedia learning object. Specialists and students validated the obtained product. Results: the multimedia product was created. In addition, 97,4 % of the students reported that the product had the necessary quality and attraction to contribute to their learning and 100 % reported its usefulness, which was corroborated in the result of the grades obtained, being good in 97,4 % thereof. Conclusions: multimedia is a flexible, dynamic, clear, objective and easy to understand educational resource; addressing a relevant topic for Stomatology, fulfilling the objective for which it was conceived.